2018
DOI: 10.1111/aas.13214
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical complications of central venous catheter insertions: A retrospective multicenter study of incidence and risks

Abstract: In this retrospective, multicenter observational study on 10 949 central venous catheter insertions, mechanical complications were rare. Preprocedural coagulopathy, number of needle passes, and arterial puncture were associated with grade 2-4 bleeding. Subclavian vein insertions, arterial puncture, and chronological order of the central venous catheter insertion were associated with pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 32 publications
4
68
1
4
Order By: Relevance
“…In about half of these cases, the patients suffered permanent injury of varying degree, which is notable both from an individual and socio‐economical perspective. Taking into consideration the expected incidence of CVC‐complications related to insertion and removal, the reported cases during this time period of seven years are very few . We suspect that far from all severe complications are reported to Löf, which makes it difficult to draw any conclusion on the actual occurrence of these conditions in Sweden during the study period.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In about half of these cases, the patients suffered permanent injury of varying degree, which is notable both from an individual and socio‐economical perspective. Taking into consideration the expected incidence of CVC‐complications related to insertion and removal, the reported cases during this time period of seven years are very few . We suspect that far from all severe complications are reported to Löf, which makes it difficult to draw any conclusion on the actual occurrence of these conditions in Sweden during the study period.…”
Section: Discussionmentioning
confidence: 95%
“…However, the total number of patients permanently disabled due to avoidable injuries, cannot be ignored, and should spur further work to reduce the incidence. In a recently published retrospective multicentre study from the south of Sweden on 11 000 CVC‐insertions, an incidence of serious mechanical complications of 0.2% was found . These severe complications could be considered as very rare incidents but an extrapolation gives that about 20 serious mechanical CVC‐complications would occur annually in Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jug-ular, subclavian, and femoral veins are the major insertion sites. The reported incidence of mechanical complications following central venous catheterization is between 1.1% and 17% and depends on its definition [1]. Among the most frequently reported mechanical complications are accidental artery puncture, bleeding, hematoma, pneumothorax or hemothorax.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of accidental CCA puncture may be related to anatomic variations of the IJV, specifically, its shape and relationship to the artery. However, in some retrospective design studies, the incidence of artery puncture was not reported [1]. The traditional anatomical landmark approach is used to find the correct place in which to insert catheters.…”
Section: Introductionmentioning
confidence: 99%